2018
DOI: 10.1093/mnras/sty980
|View full text |Cite
|
Sign up to set email alerts
|

On the kinematics of a runaway Be star population

Abstract: We explore the hypothesis that B type emission-line stars (Be stars) have their origin in mass-transfer binaries by measuring the fraction of runaway Be stars. We assemble the largest-to-date catalogue of 632 Be stars with 6D kinematics, exploiting the precise astrometry of the Tycho-Gaia Astrometric Solution (TGAS) from the first Gaia Data Release. Using binary stellar evolution simulations, we make predictions for the runaway and equatorial rotation velocities of a runaway Be star population. Accounting for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 78 publications
3
43
3
Order By: Relevance
“…We find no evidence of runaway RSGs, which have RVs offset by more than 30 km s −1 compared to the surrounding population (Blaauw 1961;Eldridge et al 2011;Boubert & Evans 2018;Renzo et al 2018). Based on the binary supernova scenario, Renzo et al (2018) found that the number of runaway stars is dwarfed by an order of magnitude by the number of slower moving -nevertheless unbound -walkaway stars.…”
Section: Radial Velocity Analysiscontrasting
confidence: 46%
“…We find no evidence of runaway RSGs, which have RVs offset by more than 30 km s −1 compared to the surrounding population (Blaauw 1961;Eldridge et al 2011;Boubert & Evans 2018;Renzo et al 2018). Based on the binary supernova scenario, Renzo et al (2018) found that the number of runaway stars is dwarfed by an order of magnitude by the number of slower moving -nevertheless unbound -walkaway stars.…”
Section: Radial Velocity Analysiscontrasting
confidence: 46%
“…Blaauw (1961) introduced the term "runaway stars" for those in the fast tail of the velocity distribution for a given spectral type. The typical threshold adopted to define the tail of this distribution for O and B-type stars is v 30 km s −1 (e.g., Blaauw 1956;Gies & Bolton 1986;De Donder et al 1997;Hoogerwerf et al 2000Hoogerwerf et al , 2001Dray et al 2005;Eldridge et al 2011), although sometimes other values have been considered (e.g., 40 km s −1 in Blaauw 1961;de Wit et al 2005;Boubert & Evans 2018). However, as we will argue based on simulations presented in this work, the majority of unbound companions are expected to exhibit velocities well below these thresholds.…”
Section: Introductionmentioning
confidence: 88%
“…Various earlier studies have discussed the evolution and interaction of populations of massive binary systems. Examples include, but are not limited to, Vanbeveren (1982), De Donder et al (1997, Fryer & Kalogera (1997, 2001, Fryer et al (2012), Belczynski et al (2012), Repetto et al (2012), Fragos et al (2013), Grudzinska et al (2015), Boubert & Evans (2018). Most of these studies focus on the minor fraction of systems that remain bound and are the progenitors of X-ray binaries and/or gravitational wave sources.…”
Section: Amentioning
confidence: 99%
See 1 more Smart Citation
“…In observations of open star clusters, it has been found that Be stars already have high angular momentum when they reach the zero-age main sequence (Martayan et al 2007, and references therein). However, it has also been variously suggested (Pols et al 1991;Harmanec et al 2002;Boubert & Evans 2018, and references therein) that binarity plays a formative role in the Be phenomenon. In fact, Be stars with subluminous companions (Wang et al 2018) and Be X-ray binaries with compact companions (Reig 2011) prove that there are Be stars that must have gone through a phase of strong interactions with these companion stars.…”
Section: Binaritymentioning
confidence: 99%